Enhanced Expression of Fibroblast Growth Factor Receptor 3 IIIc Promotes Human Esophageal Carcinoma Cell Proliferation. (January 2016) - Ueno, Nobuhiro; Shimizu, Akio; Kanai, Michiyuki; Iwaya, Yugo; Ueda, Shugo; Nakayama, Jun; Seo, Misuzu Kurokawa
Deregulated expression of fibroblast growth factor receptors (FGFRs) and their ligands plays critical roles in tumorigenesis. The gene expression of an alternatively spliced isoforms of FGFR3, FGFR3IIIc, was analyzed by RT-PCR in samples from patients with esophageal carcinoma (EC), including esophageal squamous cell carcinoma (ESCC) and adenocarcinoma (EAC). The incidence of FGFR3IIIc was higher in EC [12/16 (75%); p =0.073] than in non-cancerous mucosa (NCM) [6/16 (38%)]. Indeed, an immunohistochemical analysis of early-stage ESCC showed that carcinoma cells expressing FGFR3IIIc stained positively with SCC-112, a tumor marker, and Ki67, a cell proliferation marker, suggesting that the expression of FGFR3IIIc promotes cell proliferation. We used EC-GI-10 cells endogenously expressing FGFR3IIIc as a model of ESCC to provide mechanistic insight into the role of FGFR3IIIc in ESCC. The knockdown of endogenous FGFR3 using siRNA treatment significantly abrogated cell proliferation and the overexpression of FGFR3IIIc in cells with enhanced cell proliferation. EC-GI-10 cells and ESCC from patients with EC showed endogenous expression of FGF2, a specific ligand for FGFR3IIIc, suggesting that the upregulated expression of FGFR3IIIc may create autocrine FGF signaling in ESCC. Taken together, FGFR3IIIc may have the potential to be an early-stage tumor marker and a molecular target for ESCC therapy.